Development of a cornering bench fatigue test for the validation of a lightweight commercial vehicle front hub - YAYLA, PAŞA (Springer New York LLC, 2011)
Laboratory testing to validate the performance of vehicle components is a common practice in the automotive market. However, during standard bench testing of a commercial front wheel hub, several failures occurred in unexpected regions indicating an inconsistency with the vehicle cornering tests. This article addresses this inconsistency and presents methods for fatigue assessment using an accelerated rig (bench) test for a lightweight commercial vehicle front wheel hub. A complete cornering (figure of eight) vehicle test is modeled on a multi-body dynamic simulation system (ADAMS/Chassis) and the results are compared with the actual data obtained from the hub of a vehicle instrumented with a set of wheel force transducers. The multi-axial loading condition is successfully simplified due to the dominance of some stress components. Load data from the simulation are processed with the rain flow cycle counting algorithm. Critical locations on the C55 steel hub are determined with the stress analysis done on ANSYS (ANSYS Theory Reference: Release 10.0, 2005). Total damage is estimated by using the Palmgren-Miner linear damage summation rule. Finally, some validation test results are consistent with vehicle tests and may be used to substitute performance. © 2011 ASM International.
Keywords: Automotive design; Automotive failures; Fatigue life; Vehicle failures